Effects of Different Phosphorus Fertilizer Levels on Growth and Yield Components of Chickpea (Cicer-arietinum L.) - Maaruf, Karwan Fatah; Saeed, Nask Ahmed; Tahir, Nawroz Abdul-razzak (Sulaimani Journal for Pure and Applied Sciences, 2021)
From the winter seasons 2018-2019 and 2019-2020, a field experiment was conducted at the Directorate of Agricultural Research Sulaimani in the Kurdistan province of Iraq to evaluate the various levels of phosphorus control, 25, 50, 75, and 100 P2O5 kg ha-1 as triple superphosphate on the growth and yield components of chickpea (Cicer arietinum L.) by using a randomized complete block design (RCBD). Based on a statistical analysis of variance conducted over the two years the influence of various phosphorus analyses had no significant effects on the plant height, number of branches per plant and protein content. Whereas, in both years, the effect of different phosphorus levels application had a significant effect on the number of pods per plant, the number of grains per plant, 100-grain of weight, gains of weight, and grain yield. According to best output, the results showed that 100 P2O5 kg ha-1 had the best positive effect during the two-year study.
Keywords: Chickpea; phosphorus; growth; production components